Legal and regulatory framework of Islamic microfinance in Liberia : lessons from Bangladesh and Indonesia - Fofana, Ibrahim Vamba (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
The current legal and regulatory framework of microfinance in Liberia is structured on the conventional microfinance system, which offers interest-bearing loans and focuses mainly on women. This system does not satisfy the needs of the greater number of the poor in the country and Muslims in particular. This phenomenon inherently calls for a reform of the legal and regulatory framework of Islamic microfinance as a vibrant tool to alleviate poverty in the country. This research therefore aims to examine the possibility of introducing the Islamic microfinance system within the extant laws of Liberia, after evaluating the lessons learned from the legal and regulatory framework of the Islamic microfinance in Bangladesh and Indonesia. The research employed a qualitative research methodology and used an inductive method in data analysis. The data collected and analysed from Islamic and conventional sources. The Islamic sources include the Qur'an, Sunnah, Tafsir, commentaries of the Sunnah, books of Islamic jurisprudence, books on Islamic microfinance, journal articles, theses and conference proceedings. The conventional sources cover the constitutions of the three jurisdictions studied in this research and relevant statutes, law books, textbooks on microfinance, journal articles, newspapers and online materials on Liberia, Bangladesh and Indonesia. Findings of the research reveal that there is no legal and regulatory framework for Islamic microfinance in Liberia and that this has deprived Muslims who are particularly excluded from the conventional microfinance sector. The research has also found that Liberia has a lot to learn from the legal and regulatory framework of Islamic microfinance in Bangladesh and Indonesia respectively. Therefore, the research recommends setting up a body to regulate Islamic microfinance in Liberia in consultation with the Central Bank of Liberia (CBL) as well as setting up a Shari'ah Committee to ensure that the modes of Islamic microfinance institutions are truly Shari'ah compliant. The research further proposes the enactment of a special law for Islamic microfinance and establishing the Shari'ah Advisory Council for Islamic microfinance in Liberia. The research further suggests having diversified sources of funding like zakah and waqf for Islamic microfinance institutions in Liberia. The findings conclude that the Islamic microfinance system is a viable alternative to the conventional microfinance system in the country, because it appeals to both Muslims and non-Muslims in Liberia. But, it requires a robust legal and regulatory framework to effectively operate in the country.